MAKNA KEESAAN DAN METAFISIKA KETUHANAN DALAM ISLAM PERSPEKTIF IBNU RUSYD - Shintia Faradina; Iqbal Kholidi (AL-BAYAN INSTITUTE, 2022)
This paper discusses the dialectical thoughts of Ibn Rushd and theologians on divine metaphysics. The discussion is based on the study of criticisms and dialogues on the theologians’ view on metaphysics. Three important points emerge: firstly, how Ibn Rushd presented the basis of his critical arguments; secondly, the process of Ibn Rushd’s methods of criticism on the theologians’ metaphysical reasons and lastly, the content of Ibn Rushd’s criticisms of the theologians’ metaphysical reason. This paper provides a detailed description of the themes as accurate and comprehensive ways to provide a basis of Ibn Rushd’s criticism. This study contributes to encouraging and changing the views of scholars of Islamic theology that Ibn Rushd, apart from being a philosopher, is also a critical thinker in the field of Islamic theology.